A psicologia do corpo e as fronteiras da identidade contemporânea - Leitner, Priscilla de Castro Campos (2014)
This work is an addition to a notable and growing scientific output turns to examine the body, not only as an object of construction and historical research, but from the perspective of the relations of sociability and alterity. This is to consider the changes of contemporary subjectivities and identities in the construction and constitution of the body which plays a central role. Taking the body as an epistemological and anthropological fact, we seek an understanding of the psychology of the body in order to understand the identity of the body as a way to discover contemporary individual in relation to the world.